Internationalisation strategies of African MNEs: a case analysis of Angolan and Mozambican enterprises. (22nd August 2019) - Goncalves, Marcus; Smith, Erika Cornelius
This study investigates the internationalisation strategies of Lusophone Africa multinational enterprises (LAMNEs) from Angola and Mozambique. While previous scholarship examining the investment decisions and actual investment commitments found that MNEs make choices to internationalise incrementally to reduce uncertainty, this research expands this body of scholarship by identifying Angolan and Mozambican MNEs that were born global or created to become international new ventures (INVs). Key implications of this study suggests that despite several disadvantages faced by entrepreneurs in frontier economies, particularly in Angola and Mozambique LAMNEs relied on external resources to launch themselves into international markets, utilising web-enabled digital and virtual resources, such as the Internet, social media and online professional communities of practice. In addition, most did not enter foreign markets alone and chose to rely on modes of entry that included joint ventures and partnerships, mergers and acquisitions (M&A), e-commerce, and e-business.